Innovative ecosystems and smart specialization in the European experience of spatial development of Ukraine - Pereguda, Yuliya (Human Geography Journal, 2025)
The article presents a comprehensive study of the theoretical and methodological foundations for integrating Innovation Ecosystems (IES) and Smart Specialisation Strategies (S3) as pivotal instruments of spatial development and post-war recovery in Ukraine. It traces the evolution of the European innovation policy from regional innovation systems to network-based ecosystems structured through Triple, Quadruple and Six-Helix models of cooperation. Drawing on case studies from Catalonia, Lombardy, Southern Denmark, Estonia and Lithuania, the paper identifies the core conditions for effective S3 implementation: multi-level governance, the Entrepreneurial Discovery Process (EDP), and the place-based approach that anchors innovation in local assets and networks. The research highlights Ukraine’s structural constraints – institutional fragmentation, insufficient data infrastructure, weak trust among key stakeholders, and growing security vulnerabilities resulting from hybrid warfare and cyber threats. A conceptual framework of Place-Based Innovation Hubs (PBIH) is proposed, merging S3 and IES principles into a cyclical process of regional transformation comprising asset auditing, integration, pilot testing, and digital monitoring. The model identifies IT hubs (Kyiv, Lviv, Kharkiv), green-energy hubs (Dnipro, Zaporizhzhia), and logistics-tourism hubs (Odesa, the Carpathians, frontline regions) as potential anchors of innovation-driven growth. Quantitative projections suggest that this framework could increase non-capital regional GDP by 10–15%, raise R&D spending above 1% of GDP, and integrate Ukrainian actors into Horizon Europe and EIT networks. The study contributes to the theoretical advancement of spatially embedded innovation policies and provides actionable recommendations for state institutions, local governments, and academic-industrial partnerships aimed at strengthening Ukraine’s resilience and European integration through innovation.